Asymmetric synthesis of the fully elaborated pyrrolidinone core of oxazolomycin A. - Donohoe, T; O'Riordan, T; Peifer, M; Jones, C; Miles, T (2012)
The asymmetric synthesis of the key pyrrolidinone core, including a highly elaborated exocyclic carbon chain, of the γ-lactam β-lactone antibiotic oxazolomycin A is described. Principal features include the Birch reduction of an aromatic pyrrole nucleus, a late stage RuO(4) catalyzed pyrrolidine oxidation, and a highly diastereoselective organocerium addition to an aldehyde.